A sociological analysis of a controversy in french sport science field: how to manage teams specialising in technological innovation - Terral, P.; Collinet, C. (The Engineering of sport 7, Volume 1, 2008)
A Sociological Analysis of a Controversy in French Sport Science Field. This paper aims at presenting a scientific controversy in the world of French sport sciences. It focuses upon electrical stimulation, a technique used to increase muscle with an electrical device sending electric impulses into the muscle, This technique was the subject of many scientific research studies, but the results stemming from them are contradictory, and thus create a typical controversy. This controversy involves several categories of actors, which this paper identifies while studying the type of arguments developed to impose one's point of view. Through the analysis of 50 scientific papers and 15 Interviews of the main researchers involved in the controversy, this paper studies the social processes at work in the construction and resolution of the controversy. The latter engages various conceptions of scientific research, and particularly enhances the conflicts between fundamental and applied science. The controversy is also grounded upon axiological positions and values, notably various conceptions of competitive sport, or the relationship between research and the sport industry. In addition, this paper shows how the conflicts can be better understood if one considers the researchers' social stances in the French sport science field and the interests associated with these stances. This article is relevant to the field of sports engineering as it delineates the origins of the tensions between the different actors in the world of sports and, in doing so, it offers perspectives to optimise these actors' relationships. In this respect, sociological studies provide useful knowledge on how to maximize the management of teams specializing in technological innovation.